Creation of cooperation networking between rural entrepreneurs through ICT: the case of ARTEMUR platform (Spain) - González Sánchez, Rocío; García Muiña, Fernando Enrique (Sociedad y Economía, 2011)
Women who live in small towns, with a strong agricultural character, have been affected by conditions and limitations of space in which they live. Women´s associations have been one of the most remarkable at the time to encourage and facilitate the participation of women, influencing the economic and social development in rural areas. The main objective of this study is to analyze the functions developed business networks through cooperatives case analysis of the commercial distribution platform ARTEMUR, boosted by new technologies. The article proposes a model for more exploratory learning from two perspectives –individual learning and communication–, which integrates key success factors in the current framework.